SNI ISO/IEC 27001 dan Indeks KAMI: Manajemen Risiko PUSDATIN (PUPR) - Piski Sundari; Wella Wella (ULTIMA InfoSys, 2021)
Pusdatin of the Ministry of Public Works and Public Housing is an institution that manages data and information to support management within the ministry of public works. This research was conducted to evaluate the maturity of agencies prior to conducting an external audit of ISO 27001: 2013 certification. The method used in this research is PDCA (Plan-Do-Check-Act) using our index and ISO 27001, the technicality of this research starts from a check for analysis of current conditions, Act is carried out for assessment of the WE index, Plan compares our index results with ISO 27001, and Do control recommendations for improvement. The results of this evaluation show that PUSDATIN stopped at level I + in yellow area and overall PUSDATIN stated, "Needs improvement". In conclusion, Pusdatin is not ready for an external audit of ISO 27001: 2013 certification. The aforementioned results form the basis for the recommendations made from the findings of the WE index and compared with the ISO 27001 control. Index Terms—audit keamanan informasi; indeks KAMI; ISO 27001:2013; tingkat kematangan SMKI